The role of the striatum in social behavior - Báez-Mendoza, Raymundo; Schultz, Wolfram (Frontiers in Neuroscience, 2013)
Where and how does the brain code reward during social behaviour? Almost all elements of the brain’s reward circuit are modulated during social behaviour. The striatum in particular is activated by rewards in social situations. However, its role in social behaviour is still poorly understood. Here we attempt to review its participation in social behaviours of different species ranging from voles to humans. Human fMRI experiments show that the striatum is reliably active in relation to others’ rewards, to reward inequity and also while learning about social agents. Social contact and rearing conditions have long-lasting effects on behaviour, striatal anatomy and physiology in rodents and primates. The striatum also plays a critical role in pair-bond formation and maintenance in monogamous voles. We review recent findings from single neuron recordings showing that the striatum contains cells that link own reward to self or others’ actions. These signals might be used to solve the agency-credit assignment problem: the question of whose action was responsible for the reward. Activity in the striatum has been hypothesized to integrate actions with rewards. The picture that emerges from this review is that the striatum is a general-purpose subcortical region capable of integrating social information into coding of social action and reward.